DOES VICTIMLESS DAMAGE EXIST? - Cabezas, Mar (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2020)
This article aims to explore the concept of victimless damage. This refers to paradoxical cases where a perpetrator and a moral wrong can be easily identified, but where somehow the role of the victim as such can be questioned. In order to explore this concept, I will first offer a typology of cases that could be labelled under this umbrella concept—namely, (1) cases of deceased victims, (2) biotechnological or no-identity cases, and (3) the ones related to lack of awareness due to epistemic injustice. Then, after highlighting the common traits and discussing some fuzzy cases, I will flesh out the main arguments for and against of the existence of and need for this concept, on the basis of both moral objectivism and subjectivism. In my view, delving into these arguments could shed some light on the metaethical debate on the sine qua non conditions of moral damage and its relation to moral wrongness. Finally, I will conclude by advocating for the need to introduce a gradational concept of moral damage and the second-person perspective into moral philosophy in order to take into account potential cases of victimless damage, but without having to accept the premises of moral realism.